METROLOGICAL SUPPLY OF MEASUREMENTS - Khaydarova Mukhtasar Odiljon kizi; Masharipov Shodlik Masharipovich (Web of Journals Publishing, 2024)
This article addresses the topic of metrological support in measurements, highlighting its scientific and technical significance in ensuring the accuracy, correctness, and reliability of measurement results. The article discusses the primary tasks, systems, and regulatory frameworks involved in metrological support and explains the calibration systems used to enhance the reliability of measurements. Additionally, the processes of calibration, certification, and standardization necessary for improving measurement efficiency are outlined. Errors encountered during the measurement process and their correction methods are analyzed, providing strategies to make measurement results more reliable. This article underscores the importance of metrological support in scientific research, industrial applications, and technological processes to ensure precise and dependable measurement results.
Keywords: Metrological support, Measurement tools, Calibration, Certification, Standardization, Measurement errors, Accuracy and reliability, Measurement systems, Regulatory and legal framework, Industrial applications, International standards, Measurement methods, Measurement results, Random errors, Systematic errors, Accreditation.